INTERACTIVE LEARNING INNOVATIONS TO BUILD STUDENT LEARNING ACTIVITY: A LITERATURE REVIEW 2020-2025 - Leny Puspita; Fahrur Rozi; Bambang Subali; Ellianawati (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to systematically review the literature on the implementation of interactive learning innovations in the 2020–2025 period and provide practical recommendations for their implementation in schools. The study used a systematic literature review approach with reference to the PRISMA framework. Data were collected from various databases and scientific sources, with a total of 1,219 articles identified. The selection process was carried out through screening, feasibility assessment, and quality evaluation, resulting in 65 relevant articles for further analysis. The study findings indicate that the use of digital technology, the implementation of project-based learning models, gamification strategies, and collaborative platforms consistently improve student learning engagement by increasing intrinsic motivation, interaction, and collaboration among students. However, this study also identified several obstacles, such as limited technological facilities, teacher readiness to integrate learning technology, and variations in students' adaptability to digital systems. Therefore, ongoing training for teachers, institutional policy support, and the integration of technology-based pedagogy into the curriculum are needed to create a more participatory, inclusive, and collaborative learning environment in the digital era.